1988
DOI: 10.4315/0362-028x-51.5.384
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Fecal Coliforms and Serovars of Enteropathogenic Escherichia Coli in Naturally Contaminated Cheese

Abstract: A survey of 60 cheese samples from three different manufacturers and marketed in Mosul were analyzed during the summer of 1987 for fecal coliform counts and also for the presence of enteropathogenic Escherichia coli. Among these samples there was a wide variations in counts, which ranged from <10 to 26000/g while the average ranged from 500 to 14000/g. Only 43 E. coli isolates were recovered from the cheese. Four of them agglutinated with antisera used to screen for classical enteropathogenic sero types. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…A variety of animals, such as cattle, goats, sheep, chickens, and pigeons are known to be vehicles of EPEC strains [26]; these, as well as human sources, could likely be the origin of the serogroups we found in our samples. Interestingly, our results were comparable to reported prevalence of EPEC in dairy products where O111, O86, O125, O119, and O111, O126, O128, O26, O25, O125 were commonly isolated in Iraq [27] and Egypt [28], respectively. Such observations indicate the likelihood of the agricultural production system as a primary source of contamination of raw vegetables.…”
Section: Serotypingsupporting
confidence: 89%
“…A variety of animals, such as cattle, goats, sheep, chickens, and pigeons are known to be vehicles of EPEC strains [26]; these, as well as human sources, could likely be the origin of the serogroups we found in our samples. Interestingly, our results were comparable to reported prevalence of EPEC in dairy products where O111, O86, O125, O119, and O111, O126, O128, O26, O25, O125 were commonly isolated in Iraq [27] and Egypt [28], respectively. Such observations indicate the likelihood of the agricultural production system as a primary source of contamination of raw vegetables.…”
Section: Serotypingsupporting
confidence: 89%
“…Most prevalent serogroups found in milk and milk products in Egypt are O111, O126, O128, O26, O25 and O125 [20,28]. In Iraq, four EPEC serogroups, including O111, O86, O125 and O119, are commonly isolated from cheese samples [29]. In the present investigation all EPEC serogroups were found in the soft variety sweetmeat samples tested and O55 was the most frequent one (23.66%).…”
Section: Discussionmentioning
confidence: 78%
“…In the present investigation all EPEC serogroups were found in the soft variety sweetmeat samples tested and O55 was the most frequent one (23.66%). Contamination of dairy products by EPEC strains has been investigated and O126, O128, O25 and O125 were isolated [20,29]. It was observes that O55 EPEC serogroup is one of most prevalent in children diarrhea in Brazil [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on milk and/or dairy products showed similar results both in Brazil 3,6,9,17 and other countries. 1,5,8 It was observed that types B and C milk of brand III had a high coliform level (Figure) although EPEC strains prevailed in samples of brand II (Table 3). EPEC strains were also found in samples of brand I ( Table Table 2 Figure -Enumeration of total and fecal coliforms above the levels permitted by SNVS 12 (1997) in pasteurized milk samples.…”
Section: Discussionmentioning
confidence: 99%